Micro‐CT reconstruction reveals the colony pattern regulations of four dominant reef‐building corals. Issue 22 (4th November 2021) - Li, Yixin; Liao, Xin; Bi, Kun; Han, Tingyu; Chen, Junyuan; Lu, Jing; He, Chunpeng; Lu, Zuhong
Abstract: Colonies are the basic geometric building blocks of coral reefs. However, the forming regulations of both colonies and reefs are still not understood adequately. Therefore, in this study, we reconstructed 25 samples using high‐resolution micro‐computed tomography to investigate coral growth patterns and parameters. Our skeleton and canal reconstructions revealed the characteristics of different coral species, and we further visualized the growth axes and growth rings to understand the coral growth directions. We drew a skeleton grayscale map and calculated the coral skeleton void ratios to ascertain the skeletal diversity, devising a method to quantify coral growth. On the basis of the three‐dimensional (3D) reconstructions and growth parameters, we investigated the growth strategies of different coral species. This research increases the breadth of knowledge on how reef‐building corals grow their colonies, providing information on reef‐forming regulations. The data in this paper contain a large amount of coral growth information, which can be used in further research on reef‐forming patterns under different conditions. The method used in this study can also be applied to animals with porous skeletons. Abstract : In this study, we use high‐resolution micro‐computed tomography to reconstruct 25 representative coral samples, indicating that there is a polyp network supported by the canal system within coral skeletons, which maintains coral growth. We visualized coral growth regulations to highlight the similarities and differences among different genera, and investigated different growth strategies by their skeleton‐forming patterns. Growth parameters of coral skeletons were obtained being on the gray scale of 3D reconstructions to reveal the mineralizing diversity among species.